Volume 2: ASME 2016 Energy Storage Forum 2016
DOI: 10.1115/es2016-59190
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Basic Properties of Ternary Eutectic Chloride Salts Used as High Temperature Heat Transfer Fluids and Thermal Storage Media

Abstract: Concentrated solar power (CSP) technologies tend to work at more and more high temperatures, which correspondingly need a high temperature heat transfer fluid (HTF) to transmit the heat from solar concentrator to power plant. The objective of this work is to study heat capacities of a HTF which can work at upper limit temperature of around 850 °C. The ideal HTF should have low melting temperature and be thermally stable at high temperatures. High specific heat capacity is also favorable. The eutectic ternary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The measurements of melting point, heat of fusion, and the specific heat capacity were carried out using a simultaneous differential scanning calorimetry and thermogravimetric analysis (TG) system (Model STA449 F3 made by NETZSCH). The reliability of this system was checked in our previous work for the measurement of eutectic salts NaCl-KCl-ZnCl 2 [18]. The results in that work showed that the difference in melting point and the deviation of the heat of fusion were below 61 C and 4.5%, respectively, when compared to data in literature [18].…”
Section: Differential Scanning Calorimetry Test For Meltingmentioning
confidence: 91%
See 1 more Smart Citation
“…The measurements of melting point, heat of fusion, and the specific heat capacity were carried out using a simultaneous differential scanning calorimetry and thermogravimetric analysis (TG) system (Model STA449 F3 made by NETZSCH). The reliability of this system was checked in our previous work for the measurement of eutectic salts NaCl-KCl-ZnCl 2 [18]. The results in that work showed that the difference in melting point and the deviation of the heat of fusion were below 61 C and 4.5%, respectively, when compared to data in literature [18].…”
Section: Differential Scanning Calorimetry Test For Meltingmentioning
confidence: 91%
“…The reliability of this system was checked in our previous work for the measurement of eutectic salts NaCl-KCl-ZnCl 2 [18]. The results in that work showed that the difference in melting point and the deviation of the heat of fusion were below 61 C and 4.5%, respectively, when compared to data in literature [18].…”
Section: Differential Scanning Calorimetry Test For Meltingmentioning
confidence: 91%
“…The melting point and specific heat capacity of the MgCl2-KCl samples were measured using a simultaneous differential scanning calorimetry and thermogravimetric analyses system (STA449 F3 NETZSCH). The calibration of the instrument is discussed in Dehghani et al, 2016. Ten separate melting point and heat capacity measurements with fresh 32-68 mole % MgCl2-KCl samples were performed.…”
Section: Heat Capacity Measurements: Xu 2018 Mgcl2-kcl Data Setmentioning
confidence: 99%